PERAN INCREMENTAL VALIDITY SEBAGAI PEMEDIASI PADA PENGARUH PROTEAN CAREER TERHADAP CAREER OUTCOME (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta) - Maulida Purwani Chusna; Jati Waskito (JURNAL LENTERA BISNIS, 2024)
Individual orientations can differ due to personal tendencies in navigating careers and attitudes. Through this research, it was determined to set objectives to measure the influence of the role of incremental validity as a mediator on the influence of protean career on career outcomes. In the research, it was found through partial least square analysis measurements with a quantitative approach that a number of 100 students from the economics and business faculty at Muhammadiyah University of Surakarta were found as a sample of respondents who were then analyzed to obtain the results, namely Protean career had a positive and significant influence on incremental validity, Protean career had a positive influence and significant on career outcomes and Incremental validity as a mediator has a positive effect on protean career on career outcomes. Key words: Protean Career, Incremental Validity, Career Outcome, Student